Adjustment and Sensitivity Analyses of a Beta Global Rangeland Model - Boone, Randall B.; Conant, Richard T.; Sircely, Jason A. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
G-Range is a global model that simulates generalized changes in rangelands through time, created with support from the International Livestock Research Institute. Spatial data and a set of parameters that control plant growth and other ecological attributes in landscape units combine with computer code to represent ecological process such as soil nutrient and water dynamics, vegetation growth, fire, and wild and domestic animal offtake. The model is spatial, with areas of the world divided into square cells.